Effect of slip condition on vertical channel flow in the presence of radiation - Guria, M. (Zielona Góra: Uniwersytet Zielonogórski)
An analysis is made on the three dimensional flow of a viscous incompressible fluid through a vertical channel in the presence of radiation in slip flow regime. The right plate is subjected to an uniform injection and the left plate to a periodic suction velocity distribution. The velocity and temperature fields have been derived using the perturbation technique. It is found that the velocity decreases with the increase of the slip parameter. It is also found that the velocity decreases with the increase of the radiation parameter but near the right plate it increases. For cooling of the plate, the velocity increases with the increase of the Grashoff number and decreases near the right plate but the reverse effect is observed for heating the plate.
Keywords: three-dimensional; injection; suction; buoyancy; transpiration cooling; free convection